Strength training fundamentals in gymnastics conditioning - Major, J. J.
Strength Training Fundamentals in Gymnastics Conditioning; Consistent, special strength training is necessary for the best possible performance in gymnastics; Training to increase muscle size and strength is important, but maximum strength from minimum size is the most important training goal; Rest and recuperation